Kinetics of Oxidation of Cysteine by Bromamine-T in H2SO4 Medium - Jagadeesha, M.B.; Ananda, S.; Raman, M.G. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cysteine by sodium N-bromotoluenesulfonamide (bromamaine-T or BAT) in H2SO4 medium has beencarried out at 30°C. The effect of [H+] and [SO42- ], variation ofionic strength and dielectric constant to the medium on the rate ofreaction has been studied. Addition of the reaction product, toluenesulfonamide had no effect on the rate of reaction. Thermodynamicparameters have been evaluated by studying the kinetics at varioustemperatures. Suitable mechanism has been proposed in consistency with the kinetic results.